Endothelial dysfunction of patients with incisional hernias with concomitant morbid obesity - Piatnochka, Vladymyr; Dzyubanovsky, Ihor; Polyatsko, Konstiantyn; Svistyn, Roman; Kohan, Roman (Journal of Education, Health and Sport, 2018)
The analysis of the diagnostic value of endothelial dysfunction index of patients with postoperative ventral hernias because of morbid obesity has proved its informativeness, especially in determining the endothelium level index circulating entohelial cells (CEC) and adhesion molecules of vessel endothelium type 1 (sVCAM-1) which allowed the prediction and the appropriate correction of probable complications in the early postoperative period. Objective: to study the dynamics of endothelial dysfunction markers of patients with large incisional hernias in the consequence of morbid obesity before and after surgical interventions. Materials and methods. The investigation was performed from 2016 to 2018 and was based on the study of endothelial dysfunction and early local and general postoperative complications of 164 patients who were treated for post-operative ventral hernia in obesity. The results of investigation. Tissue hernioplasty was performed for 48 (29.27%) patients. Prosthetic plastic is executed for most operated persons 116 (70.73%), among them “Onlay” for 56 (34.15%), “Inlay” - 11 (6.71%), “Sublay” for 49 (29.87% ) patients. The separation technique of hernioplasty was conducted only for patients with giant incision hernias - 5 (3,05%). Dermatolipectomy was performed for 39 (23.78%) operated patients. Preference was given to dermatolipectomy of Jolly, Thorek 39 (19.5%) and Castansres-Goethel 7 (4.3%). The frequency of postoperative complications was high - 40.85%. Thromboembolism of the pulmonary artery arose in 0.61%, ACS - 3,05%, the recurrence of hernia - 12,20%. The analysis of endothelial dysfunction index shows a significant increase of the CEC level to 10.25 ± 1.6 cells × 104 / l (p <0.05) and sVCAM-1 to 440.4 ± 18.69 ng / ml. in the early postoperative period. The decrease in the concentration of P and E selectines which was below the preoperative levels, both in the early and late postoperative period, is a good prognostic sign, and the correction, which was made in time, reduces postoperative complications significantly. Conclusions. The markers of endothelial dysfunction CEC and sVCAM-1 can be used as a prognostic criterion of the occurrence of complications and severity of the postoperative period of patients with large inquisitive hernias as a result of morbid obesity.